PEMBERDAYAAN MASYARAKAT PEDESAAN SEBAGAI UPAYA PENCEGAHAN KOMPLIKASI HIPERTENSI PADA LANSIA - Annuril, Kheli Fitria; Kamsiah, kamsiah; Susanto, Ari (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2024)
Hypertension is a frequent, chronic and age-related disorder, which often leads to debilitating cardiovascular and renal complications. The main causes of this disease are genetics, behavior and lifestyle. Low awareness of hypertension management is a major cause of complications. Tumbuan Village, Seluma Regency is the Working Area of Tumbuan Health Center which consists of Lubuk Sandi Sub-district with an area of 141.3 Km² consisting of lowlands, highlands, rice fields and swamps. Based on the survey results, there are still 1,368 people in Tumbuan Village who suffer from hypertension, and those suffering from hypertension are mostly the elderly. For the activity plan of the activities to be carried out, this is counseling on the importance of maintaining a good diet, the aim is to provide an understanding of the importance of maintaining a diet to avoid hypertension. Partners in this service are elderly posyandu cadres in Tumbuan Village, Seluma Regency, Participants in this activity are elderly people with hypertension as many as 25 people. The methods in this activity are counseling, lectures and discussions as well as demonstrations of making traditional medicines for people with hypertension. The success of this event can be seen from the enthusiasm and enthusiasm of the elderly. The elderly also play a very active role in answering evaluations about the material that has been delivered. The implementation of the service activities was carried out smoothly, most of the 93% (14 elderly) increased their knowledge with the category of good knowledge while 6.7% (1 person) with the category of sufficient knowledge in the importance of maintaining a diet to avoid hypertension and committed to implementing all the recommendations of the service team to prevent hypertension.